(untitled) (Research, Society and Development, 2020)
Given the number of terms related to distance education, there is a need to explain these concepts. The purpose of this article is to explain the derivations of the Learnings models in Digital Distance Education (EaDD) as well as to distinguish the different functions that these models are outlining in the digital age. These derivations are known as: E-learning, B-learning, M-learning, U-learning and other variations including: MOOC, Microlearning, P-Learning, I-Learning and T-Learning. As a result, an overview of the derivations from the E-learning model and the growth and democratization of digital technologies and mobile devices was obtained. In conclusion, we reiterate the need to expand and deepen basic and applied research on learning models, derived from pedagogical models that adopt active methodologies and / or digital technologies in teaching practice, according to the specificities of the course, the pedagogical and technological resources available.